Exploring the relationship between auditory hallucinations, trauma and dissociation. Issue 3 (May 2020) - Wearne, Deborah; Curtis, Guy J.; Melvill-Smith, Peter; Orr, Kenneth G.; Mackereth, Annette; Rajanthiran, Leon; Hood, Sean; Choy, Winston; Waters, Flavie
Abstract : Background: It is clinically imperative to better understand the relationship between trauma, auditory hallucinations and dissociation. The personal narrative of trauma has enormous significance for each individual and is also important for the clinician, who must use this information to decide on a diagnosis and treatment approach. Aims: To better understand whether dissociation contributes in a significant way to hallucinations in individuals with and without trauma histories. Method: Three groups of participants with auditory hallucinations were recruited, with diagnoses of: schizophrenia (without trauma) ( n = 18), post-traumatic stress disorder (PTSD, n = 27) and comorbid schizophrenia and PTSD (SCZ+PTSD), n = 26). Clinician-administered measures included the PTSD Symptoms Scale Interview (PSSI-5), the Clinician-Administered Dissociative States Scale (CADSS) and the Psychotic Symptom Rating Scales (PSYRATS). Results: Dissociative symptoms were significantly higher in participants with trauma histories (PTSD and SCZ+PTSD groups) and significantly correlated with hallucinations in trauma-exposed participants, but not in participants with schizophrenia (without trauma history). Hallucination severity was correlated with the CADSS amnesia subscale score, but depersonalisation and derealisation were not. Conclusions: Dissociation may be a mechanism in trauma-exposed individuals who hear voices, but it does not explain all hallucinatory experiences. The SCZ+PTSD group were in an intermediary position between schizophrenia and PTSD on dissociative and hallucination measures. The PTSD and SCZ+PTSD groups experienced dissociative phenomena much more frequently than the schizophrenia group, with a significant trend towards the amnesia subtype of dissociation.